1998
DOI: 10.1002/(sici)1096-9861(19980209)391:2<214::aid-cne5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical relationships between aromatase and tyrosine hydroxylase in the quail brain: Double-label immunocytochemical studies

Abstract: The activation of male sexual behavior in Japanese quail (Coturnix japonica) requires the transformation of testosterone to 17beta-estradiol by the enzyme aromatase (estrogen synthetase). There are prominent sex differences in aromatase activity that may be regulated in part by sex differences in catecholaminergic activity. In this study, we investigate, with double-label immunocytochemistry methods, the anatomical relationship between the catecholamine synthesizing enzyme, tyrosine hydroxylase (TH) and aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…It should be noted that dopaminergic signaling could also be involved in the rapid modulation of AA. Double immunocytochemistry highlighted a close interaction between dopaminergic fibers (tyrosine hydroxylase-positive structures) and aromatase-positive cells in the hypothalamus of Japanese quail (Balthazart et al, 1998 ). More importantly, several dopaminergic drugs rapidly inhibited AA in homogenates and in vitro explants obtained from the preoptic area hypothalamus of male Japanese quail (Baillien and Balthazart, 1997 ; Balthazart et al, 2002 ).…”
Section: Rapid Modulation Of Aromatase Activitymentioning
confidence: 99%
“…It should be noted that dopaminergic signaling could also be involved in the rapid modulation of AA. Double immunocytochemistry highlighted a close interaction between dopaminergic fibers (tyrosine hydroxylase-positive structures) and aromatase-positive cells in the hypothalamus of Japanese quail (Balthazart et al, 1998 ). More importantly, several dopaminergic drugs rapidly inhibited AA in homogenates and in vitro explants obtained from the preoptic area hypothalamus of male Japanese quail (Baillien and Balthazart, 1997 ; Balthazart et al, 2002 ).…”
Section: Rapid Modulation Of Aromatase Activitymentioning
confidence: 99%
“…As true of the mammalian medial amygdala, the avian subpallial medial amygdala is reciprocally connected with the hippocampal formation (Atoji et al, 2002; Atoji and Wild, 2004). Importantly, the avian subpallial medial amygdala is enriched in sex-steroid concentrating neurons possessing estrogen and androgen receptors and the enzyme aromatase (Martinez-Vargas et al 1976; Balthazart et al, 1998; Foidart et al, 1999). Their abundance is more striking in males (Watson and Adkins-Regan, 1989), and reflects the role of the steroid receptors and the neurons that contain them in male sexual behavior (Panzica et al, 1996; Thompson et al, 1998; Absil et al, 2002).…”
Section: Four Neural Systems Occupying the Lateral Subpallial Wallmentioning
confidence: 99%
“…Immunohistochemical studies have demonstrated that there are dense networks of tyrosine hydroxylase (TH)-ir fibers in brain areas that contain aromatase-ir neurons, such as the sexually dimorphic MPOA or the bed nucleus striae terminalis (BNST) in quail. Double-labeling has confirmed that aromatase-ir cells are in close association with TH-ir fibers in quail (Balthazart et al, 1998 ). Therefore, the possible existence of a direct modulation of aromatase activity by dopamine and/or norepinephrine was systematically investigated by in vitro incubations of quail hypothalamic homogenates (Balthazart et al, 2002 ).…”
Section: Molecular Mechanisms Regulating the Activity Of Aromatase Anmentioning
confidence: 89%